2003
DOI: 10.1081/jdi-120024297
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Blood Pressure Fall in Renal Disease Patients

Abstract: Altered diurnal rhythm should not be considered as a usual complication of renal disease. Inadequate antihypertensive pharmacotherapy could be related to the abnormalities of nighttime BP fall when it is detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Absence of a normal dipping pattern has been proposed as a risk factor for progression of renal disease and cardiovascular morbidity and mortality (1)(2)(3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(20)(21)(22)(23)(24). Studies in CKD populations have demonstrated that loss of the dipping pattern is associated with increased proteinuria and accelerated progression of renal disease and poor allograft function when transplant participants were evaluated 1 year after transplantation (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absence of a normal dipping pattern has been proposed as a risk factor for progression of renal disease and cardiovascular morbidity and mortality (1)(2)(3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(20)(21)(22)(23)(24). Studies in CKD populations have demonstrated that loss of the dipping pattern is associated with increased proteinuria and accelerated progression of renal disease and poor allograft function when transplant participants were evaluated 1 year after transplantation (15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that microalbuminuria, progression of renal disease, left ventricular hypertrophy, cardiovascular mortality, and silent cerebrovascular disease are associated with higher night-time BP and are more frequent in nondippers (,10% nocturnal BP reduction) compared with dippers (.10% nocturnal reduction) (4)(5)(6)(7)(8)(9)(10) and in those with masked hypertension (11). Studies have also demonstrated that renal disease is associated with a nondipping pattern, and that nondipper patients with renal disease progress more rapidly to ESRD than dippers (8)(9)(10)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 96%
“…Thus, researchers might be advised to include measures of participants' actual times of awakening and going to sleep. Several ABPM studies have incorporated self-report diary reports of participants' waking and sleeping times (Gatzka & Schmieder, 1995;Loimaala et al, 1997;Robles, Cancho, Ruiz-Calero, Angulo, & Sanchez-Casado, 2003;Shapiro & Goldstein, 1998). The main advantage of using diary reports rather than default daynight definitions is that diary reports allow for the possibility that participants' true waking and sleeping times differ from (a) the times used to define default day and night periods and (b) other participants' waking and sleeping times.…”
Section: Design Issuesmentioning
confidence: 99%
“…There are several studies in adult patients showing that nocturnal blood pressure (BP) decrease (dip) is reduced in patients with secondary hypertension in comparison to patients with primary hypertension. [5][6][7][8][9][10][11] In children, only one study systematically investigated this issue. 12 Flynn 12 has shown in this study on 93 mostly treated hypertensive children that pediatric patients with secondary hypertension also have a blunted nocturnal BP dip compared with children with primary hypertension.…”
mentioning
confidence: 99%